New Distribution Record and Genetic Relationship of Bottlenose Wedgefish (Rhynchobatus australiae) Found in the Waters of Meulaboh, West Aceh - Bahri, Samsul; Arjayanda, Elsa; Fadli, Nur; Ramadhaniaty, Mutia; Razi, Nanda M.; Erima, Derila; Hasibuan, Muhammad B.A.F. (Aceh Journal of Animal Science, 2025)
Bottlenose Wedgefishes are fish that belong to the subclass Elasmobranchii, which are cartilaginous fish. West Aceh waters are one of the areas directly connected to the Indian Ocean. Bottlenose Wedgefish can be found in the Indian Ocean. Some information on Bottlenose Wedgefish DNA has now developed molecular approaches, which provide a fast and precise alternative to identify species. This research activity aims to report the presence of Bottlenose Wedgefish sharks (Rhynchobatus australiae) and analyze the relationship between Bottlenose Wedgefish sharks found in West Aceh with other regions. This research was conducted from October to December 2021. The specimens were taken from the Ujong Baroh Fish Landing Site (PPI), West Aceh, and analyzed at the Laboratory of Genetics and Aquatic Biodiversity, Faculty of Marine and Fisheries, Syiah Kuala University. The results of the study resulted in several conclusions, namely the Query Cover value of Meulaboh 1 and Meulaboh 2 samples of 93%. The Ident value of 99.70%-99.85% indicates that the same species is R. australiae. Thymine (T) nucleotide composition is 30.8%, Cytosine (C) is 24.9%, Adenine (A) is 27.4%, and Guanine (G) is 16.9%. Based on the results of phylogenetic tree reconstruction, the relationship between Rhynchobatus australiae Meulaboh samples 1 and 2 has a close kinship with Rhynchobatus australiae from India1, India2, India3, Malaysia1, Indonesia3, and Indonesia5. This research confirms the presence of Rhynchobatus australiae in West Aceh and establishes a close genetic link to regional populations.